Simulation of the Electrochemical Impedance in a Three-Dimensional, Complex Microstructure of Solid Oxide Fuel Cell Cathode and Its Application in the Microstructure Characterization - Goel, Vishwas; Cox, Dalton; Barnett, Scott A.; Thornton, Katsuyo (Frontiers in Chemistry, 2021)
Electrochemical impedance spectroscopy (EIS) is a powerful technique for material characterization and diagnosis of the solid oxide fuel cells (SOFC) as it enables separation of different phenomena such as bulk diffusion and surface reaction that occur simultaneously in the SOFC. In this work, we simulate the electrochemical impedance in an experimentally determined, three-dimensional (3D) microstructure of a mixed ion-electron conducting (MIEC) SOFC cathode. We determine the impedance response by solving the mass conservation equation in the cathode under the conditions of an AC load across the cathode’s thickness and surface reaction at the pore/solid interface. Our simulation results reveal a need for modifying the Adler-Lane-Steele model, which is widely used for fitting the impedance behavior of a MIEC cathode, to account for the difference in the oscillation amplitudes of the oxygen vacancy concentration at the pore/solid interface and within the solid bulk. Moreover, our results demonstrate that the effective tortuosity is dependent on the frequency of the applied AC load as well as the material properties, and thus the prevalent practice of treating tortuosity as a constant for a given cathode should be revised. Finally, we propose a method of determining the aforementioned dependence of tortuosity on material properties and frequency by using the EIS data.